Justification of violence during adolescence: Differences as a function of sociodemographic variables (European Journal of Education and Psychology, 2015)
The purpose of the study was to analyze the possible differences as a function of diverse sociodemographic variables (sex, school term, socio- economic-cultural level, type of public-private school network) in attitudes of justification of violence. With a descriptive, comparative, and correlational design, the Questionnaire of Attitudes towards Diversity and Violence was administered to a sample of 1423 adolescents aged from 11 to 17 years (670 boys, 753 girls). The results showed that: 1) boys justified violence (peer violence, domestic violence, violence against minorities) significantly more and displayed less rejection of violence; 2) In both sexes, justification of domestic violence and violence against minorities decreased with age (with school term), but there were no changes with age in justification of peer violence; 3) Male and female adolescents who scored lower in justification of the use of peer violence and domestic violence belonged to the high socio-economic-cultural level; and 4) Male and female adolescents who attended public schools justified peer violence and domestic violence more than those who attended private/subsidized schools; however, no differences were found in violence against minorities. The debate emphasizes the importance of implementing programs to inhibit justification of the use of violence, in view of the close relationship between justifying violence and performing violent behaviors.